The technological innovation of wood lamination: a hydraulic “A” metal frame structure for educational design and purpose - Redjie D. Arcadio; Rachel P. Abueme; Maria Rosario D. Gayamo; Jessa C. Bayotas; Eliza Jane A. Castillo; Catherine T. Mahinay; Tongierlyn D. Corda; Marie Antonette R. Carro; Jeffrey L. Traya (Science and Education, 2023)
This study aimed to develop and assess its acceptability and effectiveness of Technological Innovated Wood Lamination: A Hydraulic “A” Metal Structure for Educational Design and Purpose at Cebu Technological University- Pinamungajan Campus in Pinamungajan, Cebu, Philippines. The research utilized a quasi-experimental approach with a survey research design, where questionnaires were distributed to 40 BIT-IDT students, 10 MAVED students, and 10 instructors for evaluation. The data gathered were analyzed using total weighted points, weighted mean, and t-test. The study concluded that the Technological Innovated Wood Lamination: A Hydraulic “A” Metal Structure for Technology Instruction met the standards and performed each function accurately and effectively in construction instruction. The design, ergonomics, and safety features were highly acceptable, according to the survey responses. The study recommends the adoption and implementation of the Technological Innovated Wood Lamination: A Hydraulic “A” Metal Structure for Educational Design and Purpose. Furthermore, the study suggests the use of the User’s Manual to ensure the safety of the end-users. Overall, this study highlights the potential of the Technological Innovated Wood Lamination technology in enhancing construction technology instruction and promoting safety in the construction industry.